(untitled) (International journal of artificial intelligence, 2025)
Language serves as a mirror to human relationships, capturing their nuances, emotions, and complexities. English idioms, in particular, offer fascinating insights into how interpersonal connections are perceived and communicated. From friendships to conflicts, romantic bonds to misunderstandings, idioms encapsulate a wealth of cultural and linguistic heritage. idioms play a crucial role in language by expressing complex ideas in a concise and culturally rich manner. in interpersonal relationships, idioms often reflect emotions, trust, conflict, and social dynamics. this paper explores how English idioms represent different aspects of human relationships, analyzing their meanings and implications in communication.